Magnetron-sputtered copper nanoparticles: lost in gas aggregation and found by in situ X-ray scattering. Issue 38 (24th September 2018) - Kousal, Jaroslav; Shelemin, Artem; Schwartzkopf, Matthias; Polonskyi, Oleksandr; Hanuš, Jan; Solař, Pavel; Vaidulych, Mykhailo; Nikitin, Daniil; Pleskunov, Pavel; Krtouš, Zdeněk; Strunskus, Thomas; Faupel, Franz; et al.
Abstract : Formation of Cu nanoparticles inside a gas aggregation cluster source was investigated by in situ SAXS. Abstract : Magnetron discharge in a cold buffer gas represents a liquid-free approach to the synthesis of metal nanoparticles (NPs) with tailored structure, chemical composition and size. Despite a large number of metal NPs that were successfully produced by this method, the knowledge of the mechanisms of their nucleation and growth in the discharge is still limited, mainly because of the lack of in situ experimental data. In this work, we present the results of in situ Small Angle X-ray Scattering measurements performed in the vicinity of a Cu magnetron target with Ar used as a buffer gas. Condensation of atomic metal vapours is found to occur mainly at several mm distance from the target plane. The NPs are found to be captured preferentially within a region circumscribed by the magnetron plasma ring. In this capture zone, the NPs grow to the size of 90 nm whereas smaller ones sized 10–20 nm may escape and constitute a NP beam. Time-resolved measurements of the discharge indicate that the electrostatic force acting on the charged NPs may be largely responsible for their capturing nearby the magnetron.